Effective corrosion inhibition of mild steel in hydrochloric acid by newly synthesized Schiff base nano Co(ii) and Cr(iii) complexes: spectral, thermal, electrochemical and DFT (FMO, NBO) studies. Issue 50 (14th November 2022) - Melhi, Saad; Bedair, Mahmoud A.; Alosaimi, Eid H.; Younes, Ayman A. O.; El-Shwiniy, Walaa H.; Abuelela, Ahmed M.
Abstract : Two Co(ii ) and Cr(iii ) complexes were synthesized, characterized and examined as corrosion inhibitors. The electrochemical data showed high inhibition efficiencies with mixed-type behavior. FMO and NBO were considered for the computational analysis. Abstract : Two new cobalt(ii ) and chromium(iii ) complexes were synthesized and characterized by FT-IR, 1 HNMR, UV, elemental analysis, TGA, conductivity, XRD, SEM, and magnetic susceptibility measurements. Structural analysis revealed a bi-dentate chelation and octahedral geometry for the synthesized complexes. The optical band gap of the Co(ii )-L and Cr(iii )-L complexes was found to be 3.00 and 3.25 eV, respectively revealing semiconducting properties. The X-ray diffraction patterns showed nano-crystalline particles for the obtained complexes. In addition, the synthesized metal complexes were examined as corrosion inhibitors for mild steel in HCl solution. The electrochemical investigations showed a maximum inhibition efficiency of 96.60% for Co(ii )-L and 95.45% for Cr(iii )-L where both complexes acted as mixed-type inhibitors. Frontier Molecular orbital (FMO) and Natural bond orbital (NBO) computations showed good tendency of the ligand to donate electrons to the metal through nitrogen atoms while the resultant complexes tended to donate electrons to mild steel more effectively through oxygen atoms and phenyl groups. A comparison between experimental and theoretical findings was considered through the discussion.